Gerakan Desa Sehat Tanpa Rokok: Edukasi Bahaya Merokok Bagi Masyarakat - Musaidah Musaidah; Rahmat Pannyiwi; Serly Sani Mahoklory; Ferdic Sukma Wahyudin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Smoking remains a serious health problem in rural communities. High cigarette consumption increases the risk of non-communicable diseases, respiratory disorders, and places a financial burden on families. This community service activity aims to increase community knowledge and awareness of the dangers of smoking through the